PENGARUH PERSEPSI NILAI PELANGGAN DAN KEPUASAN KONSUMEN TERHADAP LOYALITAS KONSUMEN HYPERMART PAKUWON TRADE CENTER DI SURABAYA - Widjojo, Paulus Ongko (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Number of retail business will increase the competition for free, so that with the level of competition that is free of these retailers are currently required to create an advantage which in the end creates an attitude of loyalty from consumers against retail business. One of the retail business in Surabaya is Hypermart PTC. Consumer loyalty can be increased by the presence of a high value customer perception and satisfaction increased. The purpose of this study was to examine the influence of perceptions of the value of a customer and consumer satisfaction to the consumer loyalty Hypermart PTC in Surabaya. Sampling-taking techniques used are non probability sampling. The sample used was 150 people consumer Hypermart PTC in Surabaya. Analytical techniques used was multiple linear regression analysis with the help of the program SPSS. The results of this analysis indicate that the perception of the value of a customer and consumer satisfaction influence positive and significantly to consumer loyalty Hypermart PTC in Surabaya.